(untitled) ("Conference on Universal Science Research 2023", 2023)
The purpose of this study is to characterize the methods that educators employ when instructing young students in English vocabulary. This study was of the descriptive research type. Six English teachers who instruct pupils in three English classes at the elementary school level in Lubuk Basung from the third to the sixth grade participated in this study. Data for the study was gathered through interviews and observation. Every instructor was observed and interviewed, and some of the pupils chosen through purposive sampling were also interviewed. Next, a qualitative method was used to analyze the data. The results of this study demonstrated the eleven techniques that English teachers use to teach vocabulary: role-playing, reading aloud, illustrating, utilizing demonstrations, displaying real objects, drawing, associated vocabulary, translation, and lexicon, contrast, elicitation, gesture, mime-expression, and word. Teachers employ those methods to help their students expand their vocabulary. These methods allow the instructor to impart knowledge to the learner in an understandable manner.Because of their own willingness, a number of pupils are driven to learn vocabulary by reviewing the lessons and memorization of the terms.